Built to Last : Sustainability of Early Childhood Education Services in Rural Indonesia - Hasan, Amer; Jung, Haeil; Kinnell, Angela; Maika, Amelia; Nakajima, Nozomi; Pradhan, Menno (World Bank, Washington, DC, 2019)
This paper studies the sustainability of early childhood education centers established under a large-scale, donor-funded project in rural Indonesia. Analysis of quantitative and qualitative data shows that 86 percent of the centers continued to provide preschool services three years after project funding ended. Centers balanced the reduction in funding by introducing student fees. The paper estimates a series of logistic regression models to predict center sustainability. Centers that increased their share of expenditures on teacher salaries during the project were significantly more likely to remain open. Often this was made possible by centers altering their mix of supplementary services provided. Centers that provided higher quality care, had more complementary services in the area, and had more parental involvement were significantly more likely to be sustained after donor funding ended. In contrast, centers with more substitute services in the area were less likely to be sustained. There is no evidence to suggest that distance to the village center or nearest neighboring center was a major factor for sustainability. There is also no evidence to suggest that, while they were operating, closed centers catered to children from different wealth backgrounds than those that remained open. These results point to actionable lessons for the design and sustainability of future development projects.